Enhancement of banana plant regeneration by incorporating a liquid-based embryo development Medium for embryogenic cell suspension - Wong, W.C.; Jalil, M.; Ong-Abdullah, M.; Othman, R.Y.; Khalid, N. (2006)
Recovering plants from embryogenic cell suspensions is a complex process starting with somatic embryo development which is synchronised on medium lacking plant growth regulators, followed by differentiation and regeneration of plants. An improved method for high frequency recovery of banana plants was investigated by incorporating a liquid-based, embryo-development medium. The highest regeneration rate (approx. 32,000 plants ml-1 settled cell volume) was obtained using this liquid protocol. This is one of the highest scores recorded among published data on plant recovery in Musa spp. A detailed, comparative histological study has been carried out on somatic embryos developed in semi-solid or liquid-based media. Most mature embryos developed from the liquid protocol enabled differentiation and regeneration within 4 months. Over 3,000 plants are currently under field observation to establish the rate of somaclonal variation.